Maternal Experience of Multiple Hardships and Fetal Growth: Extending Environmental Mixtures Methodology to Social Exposures. Issue 1 (January 2021) - Goin, Dana E.; Izano, Monika A.; Eick, Stephanie M.; Padula, Amy M.; DeMicco, Erin; Woodruff, Tracey J.; Morello-Frosch, Rachel
Abstract : Background: Women can be exposed to a multitude of hardships before and during pregnancy that may affect fetal growth, but previous approaches have not analyzed them jointly as social exposure mixtures. Methods: We evaluated the independent, mutually adjusted, and pairwise joint associations between self-reported hardships and birthweight for gestational age z-scores in the Chemicals in Our Bodies-2 prospective birth cohort (N = 510) using G-computation. We examined financial hardship, food insecurity, job strain, poor neighborhood environment, low community standing, caregiving, high burden of stressful life events, and unplanned pregnancy collected via questionnaire administered in the second trimester of pregnancy. We used propensity scores to ensure our analyses had sufficient data support and estimated absolute differences in outcomes. Results: Food insecurity was most strongly associated with reduced birthweight for gestational age z-scores individually, with an absolute difference of −0.16, 95% confidence interval (CI) −0.45, 0.14. We observed an unexpected increase in z-scores associated with poor perceived neighborhood environment (0.18, 95% CI −0.04, 0.41). Accounting for coexposures resulted in similar findings. The pairwise joint effects were strongest for food insecurity in combination with unplanned pregnancy (−0.45, 95% CI −0.93, 0.02) and stressful life events (−0.42, 95% CI −0.90, 0.05). Poor neighborhood environment in combination with caregiving was associated with an increase in z-scores (0.47, 95% CI −0.01, 0.95). Conclusions: Our results are consistent with the hypothesis that experiencing food insecurity during pregnancy, alone and in combination with stressful life events and unplanned pregnancy, may affect fetal growth. Abstract : Supplemental Digital Content is available in the text.